An unusual combination of mature cystic teratoma and ovarian carcinoid tumour: rare case report of an ovarian synchronous tumour - Baghel, Jyoti; Sinha, Mridu; Rawat, Rajneesh; Chaudhary, Chanchal (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2026)
Synchronous bilateral ovarian tumours of the ovary are exceedingly rare entities characterized by the coexistence of two distinct neoplasms within the same anatomical site without histological intermixing. This case report presents a unique instance of a synchronous bilateral ovarian tumours comprising a mature cystic teratoma and an ovarian carcinoid tumour in a 46- year-old perimenopausal woman who presented with lower abdominal heaviness, a palpable mass, and right lower limb swelling. Radiological investigations revealed a large, complex right ovarian mass and a smaller left ovarian cystic lesion. A preoperative diagnosis of a neoplastic ovarian mass was made, and the patient underwent exploratory laparotomy. Intraoperative findings revealed bilateral adnexal masses; frozen section suggested benign pathology. Definitive surgery included total abdominal hysterectomy with bilateral salpingo-oophorectomy. Histopathological examination confirmed a mature cystic teratoma in the left ovary and a carcinoid tumour in the right ovary. Immunohistochemistry supported the diagnosis, showing CD56 positivity and a Ki-67 index of 15%. This case highlights the importance of considering synchronous bilateral ovarian tumours in the differential diagnosis of complex ovarian masses, especially when imaging reveals both solid and cystic components. Early recognition and accurate histopathological diagnosis are critical for guiding appropriate surgical management and ensuring optimal patient outcomes.